Intraocular Injection of Muscimol Induces Illusory Motion Reversal in Goldfish - Lee, Sang-Yoon (The Korean Physiological Society and The Korean Society of Pharmacology, 2009)
Induced activation of the gamma-aminobutyric acid(A) (GABA(A)) receptor in the retina of goldfish caused the fish to rotate in the opposite direction to that of the spinning pattern during an optomotor response (OMR) measurement. Muscimol, a GABA(A) receptor agonist, modified OMR in a concentration-dependent manner. The GABA(B) receptor agonist baclofen and GABA(C) receptor agonist CACA did not affect OMR. The observed modifications in OMR included decreased anterograde rotation (0.01~0.03 µM), coexistence of retrograde rotation and decreased anterograde rotation (0.1~30 µM) and only retrograde rotation (100 µM~1 mM). In contrast, the GABA(A) receptor antagonist bicuculline blocked muscimolinduced retrograde rotation. Based on these results, we inferred that the coding inducing retrograde movement of the goldfish retina is essentially associated with the GABA(A) receptor-related visual pathway. Furthermore, from our novel approach using observations of goldfish behavior the induced discrete snapshot duration was approximately 573 ms when the fish were under the influence of muscimol.